Working-class schooling in post-industrial Britain : only schools and courses - McInch, Alex (Emerald studies in the sociology of education, 2022)
Providing a historical development of the UK education system and its policies, Alex McInch offers insight on how structural decisions impact how working-class pupils view and navigate the educational field. This ethnographic investigation explores topics such as compensatory educational policies, including Free School Meals, and how these attempt to close the attainment gap between the working and middle classes. This timely book is a welcome addition to the current literature on working-class schooling in the UK and comes at a time when British society has never been more divided on a number of social issues. The landmark theories of French Socio-Philosopher Pierre Bourdieu provide a fitting framework in which to understand how young working-class people currently orientate towards education in post-industrial Britain. Also presenting thought-provoking arguments on how we need to think differently about social class in the UK, rather than using current reductionist models, this book is of interest to anyone currently working in policy, academia or education with an interest in social inequality and its supplementary effects.